KOMUNIKASI KESUKUBANGSAAN - Danang Suseno (Universitas Andalas, 2017)
This article talking about basic of society use languange is unit for do social interaction between one of human to other human in one society contects with one’s culture. Its more important different between society with one culture and society with different culture, such us sundaness which living at coastal areas, course very different with sundaness which living at hill areas, comparating with Jakarta society which is differences group ethnics society.